DEVELOPMENT OF SUSTAINABLE CULTURAL LANDSCAPES IN WEST KALIMANTAN - Karuniawan Puji Wicaksono; Nobukazu Nakagoshi (AGRIVITA, Journal of Agricultural Science, 2012)
This research focuses on investigating West Kalimantan’s traditional landscapes, shifting cultivation pattern, and comparing the forest dependency of several ethnic groups.  After conducting remote sensing and geographical information system techniques based on the satellite images LANDSAT-TM in West Kalimantan from 1996 to 2006, the decrease of primary dry tropical forest from 36.4% to 15.9% and a little increase of agriculture land from 44.8% to 45.1% were detected. West Kalimantan’s traditional landscape is a combination of primary forest, shifting dry rice-field, rubber plantation, fruits garden and home garden, meanwhile new landscape managed by migrants mainly consist of permanent wet land rice-field, dry land rice, and crop fields. The decreasing forest area forces the native people to shorten the shifting cultivation cycle or to turn to permanent agriculture with the low yield. This situation is the result in the more primary forest clearing for agriculture usage by native people and migrants. It is clear that the traditional landscape of West Kalimantan is particularly dependent upon its most vital element, the forest. Yet, traditional landscape representing the regeneration cycle of forest in West Kalimantan was constrained by changes in managed and modern landscape. Keywords: Landscape, Forest, Cultural, Land-use, Ethnics group